Peran Kepemimpinan dalam Pengembangan Kualitas Sumber Daya Manusia pada Era Revolusi 4.0 (Studi pada Sekolah Menengah Kejuruan Negeri 1 Kota Jambi) - Risa Amanda; Idham Khalik; Zainur Hidayah; Bayu Indrawan Safril; Tri Sesilia Safril; Sepriano Sepriano (Ekonomis: Journal of Economics and Business, 2023)
Management of Human Resources (HR) during the industrial revolution 4.0 is now a must for an organization to develop. Utilization of advances in information technology is one of the success factors of an organization in achieving a goal and is influenced by HR which is the driving force of various resources within an organization. Since the Covid-19 pandemic hit the world which required schools to make changes in the learning system, Jambi City Vocational School 1 has several programs in human resource development during the pandemic, including curriculum development using the blended learning method, learning using learning platforms, Learning Management System (LMS), integrated curriculum, and video conferencing. Based on the existing problems, the role of leadership in schools is expected to be able to improve the quality of human resources during the industrial revolution 4.0 at SMKN 1 Jambi City.